Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]x= \frac{-b\pm \sqrt{b^2-4ac} }{2a} [/tex] for the equation [tex]ax^2+bx+c[/tex]
Your question is [tex]x^2-2x-8=0[/tex]
So [tex]a=1 \\b=-2\\c=-8[/tex]
So plug in your numbers:
[tex]x= \frac{-(-2)\pm \sqrt{(-2)^2-4(1)(-8)} }{2(1)}[/tex]
Simplify:
[tex]x= \frac{2\pm \sqrt{4-(-32)} }{2}[/tex]
Simplify a little more:
[tex] \frac{2\pm6}{2} [/tex]
So our answer is
[tex]x= \frac{2+ 6 }{2} = 4\\x= \frac{2- 6 }{2}=-2[/tex]
So [tex]x=4, x=-2[/tex]
Your question is [tex]x^2-2x-8=0[/tex]
So [tex]a=1 \\b=-2\\c=-8[/tex]
So plug in your numbers:
[tex]x= \frac{-(-2)\pm \sqrt{(-2)^2-4(1)(-8)} }{2(1)}[/tex]
Simplify:
[tex]x= \frac{2\pm \sqrt{4-(-32)} }{2}[/tex]
Simplify a little more:
[tex] \frac{2\pm6}{2} [/tex]
So our answer is
[tex]x= \frac{2+ 6 }{2} = 4\\x= \frac{2- 6 }{2}=-2[/tex]
So [tex]x=4, x=-2[/tex]
x² - 2x - 8 = 0
x = -(-2) +/- √((-2)² - 4(1)(-8))
2(1)
x = 2 +/- √(4 + 32)
2
x = 2 +/- √(36)
2
x = 2 +/- 6
2
x = 1 +/- 3
x = 1 + 3 x = 1 - 3
x = 4 x = -2
x = -(-2) +/- √((-2)² - 4(1)(-8))
2(1)
x = 2 +/- √(4 + 32)
2
x = 2 +/- √(36)
2
x = 2 +/- 6
2
x = 1 +/- 3
x = 1 + 3 x = 1 - 3
x = 4 x = -2
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.